Silicone particle having cross-linked core, and manufacturing thereof

JP2025028989APending Publication Date: 2025-03-05WACKER CHEMIE AG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024206278
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-05

Smart Images

  • Figure 2025028989000001
    Figure 2025028989000001
  • Figure 2025028989000002
    Figure 2025028989000002
  • Figure 2025028989000003
    Figure 2025028989000003
Patent Text Reader

Abstract

To provide a particle having improved skin touch and improved mechanical stability compared to a known particle whose core contains no reinforcing filler or contains a non-reinforcing filler.SOLUTION: A particle P is composed of a core K containing a cross-linked silicone elastomer composition X and a reinforcing filler F, and a shell H of silica S. The silicone elastomer composition X is addition cross-linking, and includes (A) at least one kind of straight-chain compound containing a group having an aliphatic carbon-carbon multiple bond, (B) at least one kind of straight-chain organopolysiloxane compound having an Si-bonded hydrogen atom, or alternatively, includes, instead of (A) and (B), (C) at least one kind of straight-chain organopolysiloxane compound containing an SiC bond group having an aliphatic carbon-carbon multiple bond and an Si-bonded hydrogen atom, and (D) at least one kind of hydrosilylation catalyst.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to elastomer particles P consisting of a crosslinked silicone elastomer composition and a core comprising a reinforcing filler, and to a method for their production. [Background technology]

[0002] WO2017142068A1 describes the advantageous properties of silicone elastomer particles coated with silica, in particular the spherical properties, the possibility of affecting hydrophobic properties, friction reducing properties, and non-clogging. Therefore, this kind of silicone elastomer particles coated with silica is applied in cosmetics.

[0003] Such particles also have the advantage that they can absorb functional substances such as care oils or fragrances. This is a major advantage over the resin-based particles disclosed in WO2007113095. However, these particles according to WO2017142068 still have a non-ideal skin feel and low mechanical stability. Such elastomer particles are easily destroyed by pressure and friction. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 142068 [Patent Document 2] International Publication No. 2007 / 113095 Summary of the Invention

[0005] The present invention provides particles P composed of a core K comprising a crosslinked silicone elastomer composition X and a reinforcing filler F and a shell H of silica S.

[0006] Under application conditions, the particles P have a surprisingly improved skin feel compared to known particles that do not have a reinforcing filler in the core, which is particularly surprising since the reinforcing filler is contained in the core K of the silica-coated silicone elastomer particles and does not modify the outer shell H of the particles P which produces the direct skin feel.

[0007] Quite unexpectedly, the mechanical stability of the particles P of the invention is also improved compared to known particles whose core does not contain or does not contain reinforcing fillers, despite the fact that the outer shell H of the particles P is unchanged.

[0008] The particles P are substantially spherical. Preferably, the sphericity SPHT3, as determinable according to ISO 9276-6 using a Camsizer X2 from Retsch Technology, is at least 0.8, more preferably at least 0.82. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The particles P are particularly characterized in that the silica S used is substantially bonded to the surface of the polymer particles P. The distribution of the silica S used can be obtained from TEM micrographs of thin sections of the embedded particles of the invention. The silica S is embedded in the cross-linked polymerisation product, preferably by more than 10 nm, preferably by more than 20 nm, very preferably by more than 30 nm, in each case measured from the outer boundary of the cross-linked polymerisation product, and protrudes from the cross-linked polymerisation product, preferably by more than 10 nm, more preferably by more than 20 nm, very preferably by more than 30 nm, and is firmly bonded on the surface of the particles P. This is a major advantage over commercial products in which the finished silicone elastomer particles are post-treated with silica. In such products, the silica is not embedded in the silicone elastomer and therefore is not firmly bonded to the surface.

[0010] As silicone elastomer composition X, it is possible in principle to use all silicones known from the prior art. It is possible to use addition crosslinking compositions, peroxidic crosslinking compositions, condensation crosslinking compositions or radiation crosslinking compositions. Peroxidic crosslinking or addition crosslinking components are preferred. Addition crosslinking compositions are particularly preferred.

[0011] The addition crosslinked silicone elastomer compositions X used in the present invention are known in the prior art and in the simplest case include: (A) at least one linear compound containing a group having an aliphatic carbon-carbon multiple bond; (B) at least one linear organopolysiloxane compound having Si-bonded hydrogen atoms; or instead of (A) and (B): (C) at least one linear organopolysiloxane compound containing an aliphatic carbon-carbon multiple bond and a SiC-bonded group having a Si-bonded hydrogen atom, and (D) at least one hydrosilylation catalyst.

[0012] The addition-crosslinking silicone elastomer composition X may be a one-component silicone composition or a two-component silicone composition.

[0013] In the case of a two-component silicone elastomer composition X, the two components of the addition crosslinked silicone elastomer composition X can include all of the components in any desired combination, although typically one component does not simultaneously include a siloxane having an aliphatic multiple bond, a siloxane having a Si-bonded hydrogen, and a catalyst, i.e., does not essentially simultaneously include components (A), (B) and (D) or (C) and (D).

[0014] The compounds (A) and (B) or (C) used in the addition crosslinking silicone elastomer composition X are selected so that they are capable of crosslinking as known. Thus, for example, compound (A) contains at least two aliphatically unsaturated groups and (B) contains at least three Si-bonded hydrogen atoms, or compound (A) contains at least three aliphatically unsaturated groups and siloxane (B) contains at least two Si-bonded hydrogen atoms, or instead of (A) and (B), siloxane (C) is used which contains aliphatically unsaturated groups and Si-bonded hydrogen atoms in the above-mentioned ratio. Mixtures of (A) and (B) and (C) with aliphatically unsaturated groups and Si-bonded hydrogen atoms in the above-mentioned ratios are also suitable.

[0015] The addition-crosslinked silicone elastomer composition X typically contains 30 to 99.9 wt%, preferably 35 to 95 wt%, more preferably 40 to 90 wt% of (A). The addition-crosslinked silicone elastomer composition X typically contains 0.1 to 60 wt%, preferably 0.5 to 50 wt%, more preferably 1 to 30 wt% of (B). When the addition-crosslinked silicone elastomer composition X contains component (C), typically 30 to 95 wt%, preferably 35 to 90 wt%, more preferably 40 to 85 wt% of (C) is present in the formulation.

[0016] The compound (A) used in the present invention can include silicon-free organic compounds, preferably having at least two aliphatically unsaturated groups, and organosilicon compounds, preferably having at least two aliphatically unsaturated groups, or mixtures thereof.

[0017] Examples of silicon-free organic compounds (A) are 1,3,5-trivinylcyclohexane, 2,3-dimethyl-1,3-butadiene, 7-methyl-3-methylene-1,6-octadiene, 2-methyl-1,3-butadiene, 1,5-hexadiene, 1,7-octadiene, 4,7-methylene-4,7,8,9-tetrahydroindene, methylcyclopentadiene, 5-vinyl-2-norbornene, bicyclo[2 .2.1]hepta-2,5-diene, 1,3-diisopropenylbenzene, polybutadiene containing vinyl groups, 1,4-divinylcyclohexane, 1,3,5-triallylbenzene, 1,3,5-trivinylbenzene, 1,2,4-trivinylcyclohexane, 1,3,5-triisopropenylbenzene, 1,4-divinylbenzene, 3-methylhepta-(1,5)-diene, 3-phenylhex ... )-diene, 3-vinylhexa-(1,5)-diene, and 4,5-dimethyl-4,5-diethylocta-(1,7)-diene, N,N'-methylenebisacrylamide, 1,1,1-tris(hydroxymethyl)propane triacrylate, 1,1,1-tris(hydroxymethyl)propane trimethacrylate, tripropylene glycol diacrylate, diallyl ether, diallylamine, diallyl carbonate, N,N'-diallyl urea, triallylamine, tris(2-methylallyl)amine, 2,4,6-triallyloxy-1,3,5-triazine, triallyl-s-triazine-2,4,6(1H,3H,5H)-trione, diallyl malonate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, poly(propylene glycol) methacrylate.

[0018] The addition-crosslinking silicone elastomer composition X preferably comprises at least one aliphatically unsaturated organosilicon compound as component (A), in which case it is possible to use all aliphatically unsaturated organosilicon compounds that have been used up to now in addition-crosslinking components, such as silicone block copolymers having urea segments, silicone block copolymers having amide segments and / or imide segments and / or ester-amide segments and / or polystyrene segments and / or silarylene segments and / or carborane segments, and silicone graft copolymers having ether groups.

[0019] As the organosilicon compound (A) containing a SiC-bonded group having an aliphatic carbon-carbon multiple bond, it is preferred to use a linear or branched organopolysiloxane composed of units of the general formula (I). R 4 a R 5 b SiO (4-a-b) / 2 (I) During the ceremony, R 4 are independently in each occurrence the same or different, organic or inorganic groups that do not contain aliphatic carbon-carbon multiple bonds; R 5 are independently in each occurrence the same or different, monovalent, substituted or unsubstituted, SiC-bonded hydrocarbon radicals having at least one aliphatic carbon-carbon multiple bond; a is 0, 1, 2 or 3; b is 0, 1 or 2; However, the sum of a+b is 3 or less, and there are at least two groups R per molecule. 5 is assumed to exist.

[0020] base R 4 can include monovalent or polyvalent groups, where the polyvalent groups, such as, for example, divalent, trivalent and tetravalent groups, link two or more, such as, for example, two, three or four siloxy units of formula (I) together.

[0021] R4 Other examples of the monovalent groups are -F, -Cl, -Br, OR 6 , -CN, -SCN, -NCO, and SiC-bonded, substituted or unsubstituted hydrocarbon radicals, which may be interrupted by oxygen atoms or groups -C(O)-, and divalent radicals bonded to Si at both ends according to formula (I). 4 When contains a SiC-bonded substituted hydrocarbon group, preferred substituents are halogen atoms, phosphorus-containing groups, cyano groups, -OR 6 , -NR 6 -, -NR 6 2, -NR 6 -C(O)-NR 6 2. -C(O)-NR 6 2. -C(O)R 6 , -C(O)OR 6 , -SO2-Ph and C6F5. In these groups, R 6 are independently in each occurrence the same or different, a hydrogen atom or a monovalent hydrocarbon radical having 1 to 20 carbon atoms, and Ph is a phenyl radical.

[0022] base R 4 Examples of are methyl, ethyl, n-propyl, isobutyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl, such as n-hexyl, heptyl, such as n-heptyl, octyl, such as n-octyl and isooctyl, such as 2,2,4-trimethylpentyl, nonyl, such as n-nonyl, decyl, such as n-decyl, dodecyl, such as n-dodecyl, octadecyl, such as n-octadecyl, cycloalkyl, such as cyclopentyl, cyclohexyl, cycloheptyl and methylcyclohexyl, aryl, such as phenyl, naphthyl, anthryl and phenanthryl, alkaryl, such as o-, m-, p-tolyl, xylyl and ethylphenyl, and aralkyl, such as benzyl, α- and β-phenylethyl.

[0023] Substituted group R 4Examples of the fluorophenyl group include haloalkyl groups such as 3,3,3-trifluoro-n-propyl, 2,2,2,2',2',2'-hexafluoroisopropyl, and heptafluoroisopropyl groups; o-, m-, and p-chlorophenyl groups; -(CH)-N(R 6 )C(O)NR 6 2, -(CH2) o -C(O)NR 6 2, -(CH2) o -C(O)R 6 , -(CH2) o -C(O)OR 6 , -(CH2) o -C(O)NR 6 2. -(CH2)-C(O)-(CH2) p C(O)CH3, -(CH2)-O-CO-R 6 , -(CH2)-NR 6 - (CH2) p -NR 6 2, -(CH2) o -O-(CH2) p CH(OH)CH2OH, -(CH2) o (OCH2CH2) p OR 6 , -(CH2) o -SO2-Ph and -(CH2) o R is a haloaryl group such as -O-CF 6 and Ph correspond to the definitions given therefor above, and o and p are the same or different integers between 0 and 10.

[0024] R as a divalent radical bonded to Si at both ends according to formula (I) 4 is a group R 4 Examples of such groups are -(CH2)-, -CH(CH3)-, -C(CH3)2-, CH(CH3)-CH2-, -CH4-, CH(Ph)-CH2-, C(CF3)2-, (CH2) o -, -(CH2) o -C6H4-(CH2) o -, -(CH2) o -C6H4-C6H4-(CH2) o-, -(CH2O) p , (CH2CH2O) o , -(CH2) o -O x -C6H4-SO2-C6H4-O x -(CH2) o -, where x is 0 or 1, and Ph, o and p have the definitions given above.

[0025] base R 4 is preferably an optionally substituted monovalent SiC-bonded hydrocarbon group having 1 to 18 carbon atoms and containing no aliphatic carbon-carbon multiple bonds, more preferably a monovalent SiC-bonded hydrocarbon group having 1 to 6 carbon atoms and containing no aliphatic carbon-carbon multiple bonds, more specifically a methyl group or a phenyl group.

[0026] base R 5 can contain any desired group that is susceptible to addition reactions (hydrosilylation) with SiH-functional compounds.

[0027] base R 5 When contains a SiC-bonded substituted hydrocarbon group, preferred substituents are halogen atoms, cyano groups and -OR 6 where R 6 has the definition given above.

[0028] base R 5 preferably includes alkenyl and alkynyl groups having 2 to 16 carbon atoms, such as vinyl, allyl, methallyl, 1-propenyl, 5-hexenyl, ethynyl, butadienyl, hexadienyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, vinylcyclohexylethyl, divinylcyclohexylethyl, norbornenyl, vinylphenyl and styryl groups, with the use of vinyl, allyl and hexenyl groups being particularly preferred.

[0029] The molecular weight of component (A) may be within wide limits, e.g., 10 2 ~10 6Thus, for example, component (A) can be a relatively low molecular weight alkenyl-functional oligosiloxane such as 1,2-divinyltetramethyldisiloxane, or a relatively low molecular weight alkenyl-functional oligosiloxane having a molecular weight of, for example, 10 5 g / mol (number average determined by nmR), which have Si-bonded vinyl groups in the chain or at the end. Similarly, the structure of the molecules forming component (A) is not fixed. In particular, the structure of the relatively high molecular weight siloxanes, i.e., oligomeric or polymeric siloxanes, can be linear, cyclic, branched, or resinous or network-like. Linear and cyclic polysiloxanes are preferably represented by the formula R 4 3SiO 1 / 2 , R 5 R 4 2SiO 1 / 2 , R 5 R 4 SiO 1 / 2 and R 4 2SiO 2 / 2 It is composed of units of R 4 and R 5 has the definition given above. The branched and networked polysiloxanes further contain trifunctional and / or tetrafunctional units, preferably of the formula R 4 SiO 3 / 2 , R 5 SiO 3 / 2 and SiO 4 / 2 Of course, it is also possible to use mixtures of different siloxanes that meet the criteria of component (A).

[0030] Particularly preferred as component (A) are those having a viscosity of 0.01 to 500,000 mm, in either case measured at 25°C. 2 / sec, more preferably 0.1 to 100,000 mm 2 / sec, particularly preferably 1 to 10,000 mm 2 The use of a vinyl-functional, substantially linear polydiorganosiloxane having a DIN 53019 kinematic viscosity of 1000 / s.

[0031] As organosilicon compound (B) it is possible to use all hydrogen-functional organosilicon compounds which have also been used up to now in addition-crosslinking compositions.

[0032] As the organopolysiloxane (B) containing Si-bonded hydrogen atoms, it is preferred to use a linear, cyclic or branched organopolysiloxane comprising units of the general formula (III). R 4 c H d SiO (4-c-d) / 2 (III) During the ceremony, R 4 has the definition given above, c is 0, 1, 2 or 3; d is 0, 1 or 2; However, the sum of c+d is 3 or less, and there are at least two silicon-bonded hydrogen atoms per molecule.

[0033] The organopolysiloxane (B) used in the present invention preferably contains Si-bonded hydrogen in the range of 0.04 to 1.7 weight % (wt %) based on the total weight of the organopolysiloxane (B).

[0034] The molecular weight of component (B) may likewise be within wide limits, e.g., 10 2 ~10 6 g / mol. Thus, for example, component (B) can be a relatively low molecular weight SiH-functional oligosiloxane, such as tetramethyldisiloxane, or a polymeric polydimethylsiloxane having SiH groups in the chain or at the end, or a silicone resin containing SiH groups.

[0035] The structure of the molecules forming component (B) is not fixed. In particular, the relatively high molecular weight SiH-containing siloxanes, i.e., oligomeric or polymeric SiH-containing siloxanes, may be linear, cyclic, branched, or resinous or network-like in structure. Linear and cyclic polysiloxanes (B) are preferably represented by the formula R 4 3SiO 1 / 2 , H.R. 42SiO 1 / 2 , HR4SiO 2 / 2 and R 4 2SiO 2 / 2 It is composed of units of R 4 has the definition given above. The branched and network polysiloxanes further contain trifunctional and / or tetrafunctional units and have the formula R 4 SiO 3 / 2 , HSiO 3 / 2 and SiO 4 / 2 Preferably, R 4 has the definition given above.

[0036] It is of course also possible to use mixtures of different siloxanes which meet the criteria of component (B). Particularly preferred are low molecular weight SiH-functional compounds such as tetrakis(dimethylsiloxy)silane and tetramethylcyclotetrasiloxane, and siloxanes having a DIN 53019 kinematic viscosity at 25° C. of 1 to 20,000 mm 2 / sec, preferably 10 to 1000 mm 2 The use of high molecular weight SiH-containing siloxanes such as poly(hydrogenmethyl)siloxanes and poly(dimethylhydrogenmethyl)siloxanes, which have a molecular weight of 0.1 to 0.25 μm / sec, or similar SiH-containing compounds in which some of the methyl groups have been replaced with 3,3,3-trifluoropropyl or phenyl groups.

[0037] Component (B) is preferably present in crosslinkable silicone elastomer composition X in an amount such that the molar ratio of SiH groups to aliphatic unsaturated groups in (A) is 0.1 to 20, more preferably between 0.3 and 5.0, and particularly preferably between 0.6 and 2.

[0038] Components (A) and (B) used in the present invention are conventional products of commerce and / or can be prepared by methods common in chemistry.

[0039] Instead of components (A) and (B), the silicone elastomer composition can also contain an organopolysiloxane (C) containing aliphatic carbon-carbon multiple bonds and Si-bonded hydrogen atoms. It is also possible for the silicone elastomer composition X to contain all three components (A), (B) and (C).

[0040] When siloxane (C) is used, it is preferably composed of units of the general formulae (IV), (V) and (VI). R 4 f SiO 4 / 2 (IV) R 4 g R 5 SiO 3-g / 2 (V) R 4 h HSiO 3-h / 2 (VI) During the ceremony, R 4 and R 5 have the definitions given above for these, f is 0, 1, 2 or 3; g is 0, 1 or 2; h is 0, 1 or 2; However, there are at least two groups R per molecule. 5 and at least two Si-bonded hydrogen atoms are present.

[0041] An example of organopolysiloxane (C) is SiO 2 , known as MP resin. 4 / 2 Units, R 4 3SiO 1 / 2 Units, R 4 2R 5 SiO 1 / 2 Units and R 4 2HSiO 1 / 2 These resins are further composed of R 4 SiO 3 / 2 Units and R 4 2SiO units, R 4 2R 5 SiO 1 / 2 Units, R 42SiO units and R 4 Linear organopolysiloxanes consisting essentially of HSiO units are also possible, where R 4 and R 5 has the definition given above.

[0042] The organopolysiloxane (C) has a viscosity of 0.01 to 500,000 mm, in each case measured at 25°C. 2 / sec, more preferably 0.1 to 100,000 mm 2 / sec, especially 1~10000mm 2 It is preferred that the viscosity of the mixture be such that it has an average DIN 53019 kinematic viscosity of 1 / sec.

[0043] The organopolysiloxane (C) can be prepared by techniques common in chemistry.

[0044] As hydrosilylation catalyst (D), it is possible to use all catalysts known in the prior art. Component (D) can be a platinum group metal, such as platinum, rhodium, ruthenium, palladium, osmium or iridium, an organometallic compound, or a combination thereof. Examples of component (D) are compounds such as hexachloroplatinic (IV) acid, platinum dichloride, platinum acetylacetonate, and complexes of said compounds encapsulated in a matrix or in a core-shell type structure. Low molecular weight platinum complexes of organopolysiloxanes include 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complexes with platinum. Other examples are platinum phosphite complexes or platinum phosphine complexes. For photo- or UV-curable compositions, the photoinduced addition reaction can be initiated using, for example, alkyl platinum complexes such as derivatives of cyclopentadienyltrimethylplatinum(IV) platinum, cyclooctadienyldimethylplatinum(II), or diketonato complexes such as bisacetylacetonatoplatinum(II). These compounds may be encapsulated in a resin matrix.

[0045] In any case, component D is preferably used at a concentration of 0.1 to 1000 parts per million (ppm), more preferably 0.5 to 100 ppm, and particularly preferably 1 to 25 ppm, based on the weight of the platinum group metal and crosslinkable silicone elastomer composition X.

[0046] If the platinum group metal component is present at less than 1 ppm, the cure rate may be slow. Use of more than 100 ppm of platinum group metal may be uneconomical or may reduce the storage stability of Silicone Elastomer Composition X.

[0047] The reinforcing filler F has a BET surface area of ​​at least 50 m 2 / g of pyrogenic or precipitated hydrophobic silica, and from carbon blacks and activated carbons, such as furnace black and acetylene black, silicone resins, preferably containing at least 50 m 2 Preference is given to silicone resins F and pyrogenic and precipitated hydrophobic silicas, or mixtures thereof, having a DIN 66131 and DIN 66132 (determined with nitrogen) BET specific surface area of ​​100 / g.

[0048] Examples of silicone resins F are MQ, MT, MDQ, MDT, MTQ and MDTQ silicone resins, where M is RSiO 1 / 2 and HR2SiO 1 / 2 and R 1 R2SiO 1 / 2 D is selected from R 1 RSiO 1 / 2 and RSiO 1 / 2 and HRSiO 1 / 2 and T is selected from RSiO 3 / 2 and R 1 SiO 3 / 2 and HSiO 3 / 2 and Q is selected from SiO 4 / 2 units, where R is R 4 With the above definition of 1 is R 5 It has the definition:

[0049] The preferred pyrogenic and precipitated hydrophobic silicas are 50 to 800 m 2 / g, more preferably 100 to 500m 2 / g, particularly preferably 150 to 400m 2 / g. DIN66131 and DIN66132 BET specific surface area between 150 and 400 m 2 It is particularly preferable to use as solid F a pyrogenic hydrophobic silica having a BET specific surface area of ​​between 100 and 1500 nm / g.

[0050] The reinforcing solid F is preferably surface-treated and, as a result, hydrophobic. Thanks to the surface treatment, the preferred solid F has a carbon content of at least 1.5-20 wt.%, preferably between 1.8-10 wt.%, more preferably between 2-8 wt.%. Particularly preferred are surface-treated silicas which contain 3-6 wt.% of Si-bonded aliphatic groups. These groups are, for example, Si-bonded methyl or vinyl groups. Hydrophobic silicas suitable as solid F are characterized in that they cannot be substantially wetted with water. This means, in the context of the present invention, that the methanol number of solid F is greater than 40, preferably greater than 50.

[0051] Hydrophobized silica has been known to those skilled in the art for a long time. The solid F may be hydrophobized in a separate operating step or in the form of in-situ hydrophobization by adding a suitable hydrophobizing agent to the silicone elastomer composition X. The techniques of surface treatment and hydrophobization of silica are known to those skilled in the art. Hydrophobization is preferably carried out by halogen-free silanes, as described, for example, in EP1433749A1.

[0052] Commercially available examples of hydrophobic silica include the moiety -[Si(CH3)2-O] n HDK® H18 and HDK® H20 containing the moiety -O-Si(CH3)3 (available from Wacker Chemie AG, Munich) and AEROSIL® 972 and AEROSIL® 805 (available from Evonik Degussa GmbH, Frankfurt am Main).

[0053] In one preferred embodiment, the solid F comprises a silicone resin F, more particularly an MDT or MQ resin, preferably an MQ resin. Preferred MQ resins comprise less than 10 mol %, preferably less than 2 mol %, particularly preferably less than 0.5 mol % of D or T units. Particularly preferred MQ resins are substantially free of D or T units.

[0054] The silicone resin F is preferably solid at 25° C. under the pressure of the surrounding atmosphere, ie at 1013 hPa.

[0055] The silicone resin F is preferably a resin having a molecular weight Mw of at least 500, preferably at least 900, more preferably at least 1200, and at most 15000, preferably at most 10000, more preferably at most 8000, with a polydispersity of at most 20, preferably at most 18, more preferably at most 16 and more particularly at most 15.

[0056] Molecular weight distribution: The molecular weight distribution is determined as weight average Mw and number average Mn using the technique of gel permeation chromatography (GPC or size exclusion chromatography (SEC)) with polystyrene standards and a refractive index detector (RI detector). Unless otherwise specified, THF is used as the eluent and DIN 55672-1 is used. Polydispersity is the ratio Mw / Mn.

[0057] Preferred silicone resins F contain at least 1 mol %, preferably at least 2 mol %, of R 1 R2SiO 1 / 2 Units, R1RSiO 1 / 2 Units and R 1 SiO 3 / 2 A unit selected from the units, preferably R 1 R2SiO 1 / 2 Includes units.

[0058] The silicone resin F preferably contains from 0.1 to 10 wt. %, more preferably from 0.5 to 8 wt. %, very preferably from 1 to 6 wt. % of alkoxy groups as groups R. Methoxy, ethoxy, isopropoxy and tert-butoxy groups are particularly suitable and therefore preferred.

[0059] Preferred groups R are saturated aliphatic groups, preferably methyl, ethyl and isooctyl groups, more preferably methyl.

[0060] Preferred groups R 1 is an unsaturated aliphatic group, preferably a vinyl group.

[0061] Particularly preferred as filler F is a filler containing vinyl groups, 45 to 65 mol%, preferably 50 to 60 mol%, Q units, 30 to 50 mol%, preferably 35 to 45 mol% RSiO 1 / 2 M units of the form 1 R2SiO 1 / 2 where R is preferably methyl and R 1 is preferably vinyl.

[0062] In the crosslinkable silicone elastomer composition X, the reinforcing fillers F are preferably used as individual fillers F or, equally preferably, as mixtures of two or more fillers F.

[0063] The silicone elastomer composition X together with the reinforcing filler F forms a mixture B.

[0064] Mixture B contains 5 to 200 parts by weight, more preferably 10 to 100 parts by weight, and particularly preferably 15 to 50 parts by weight of reinforcing filler F per 100 parts by weight of crosslinkable silicone elastomer composition X.

[0065] As well as the reinforcing filler F, mixture B may also contain non-reinforcing fillers. Examples of non-reinforcing fillers are those with a BET specific surface area of ​​50 m 2 / g, for example quartz, diatomaceous earth, calcium silicate, zirconium silicate, zeolites, metal oxide powders, for example aluminum oxide, titanium oxide, iron oxide or zinc oxide and / or mixed oxides thereof, barium sulfate, calcium carbonate, gypsum, silicon nitride, silicon carbide, boron nitride, glass powders and plastic powders.

[0066] In addition to the at least one siloxane or silane, the droplets may contain a further component B selected from catalysts, fillers, inhibitors, heat stabilizers, solvents, plasticizers, colour pigments, sensitisers, photoinitiators, adhesion promoters etc.

[0067] Silica S is preferably 30 to 500 m 2 / g, more preferably 100 to 300m 2 The BET specific surface area is determined according to known methods, preferably according to German Industrial Standards DIN 66131 and DIN 66132.

[0068] The silica S is preferably surface-treated with a suitable hydrophobizing agent and is, as a result, hydrophobic. The hydrophobization should be carried out such that the silica S is still partially water-wettable. This means in the present invention that the methanol value of the silica S is less than 40, preferably less than 30. For the surface treatment, the preferred silica S has a carbon content of at least 0.2-1.5 wt%, preferably between 0.4-1.4 wt%, more preferably between 0.6-1.3 wt%. The hydrophobic group is, for example, a Si-bonded methyl or vinyl group. Techniques for hydrophobizing silica are known to those skilled in the art.

[0069] Preferred as silica S is silane-treated pyrogenic silica having a methanol number of less than 30.

[0070] Particularly preferred are partially water-wettable silicas such as those described in EP 1 433 749 A1 and DE 10 349 082 A1.

[0071] The average particle size of a granular solid F or, where appropriate, an agglomerate of particles is the average diameter d of the droplets not containing finely divided particles. 50 Smaller is preferable.

[0072] The average particle size of the granular solid F is less than 1000 nm, preferably between 10 nm and 800 nm, more preferably between 50 nm and 500 nm, very preferably between 75 nm and 300 nm, in each case measured as the average hydrodynamic equivalent diameter by photon correlation spectroscopy at 173° backscattering with a Nanosizer ZS from Malver.

[0073] For the determination of the methanol number, defined mixtures of water and methanol are prepared and the surface tension of these mixtures is then determined using known techniques. In separate experiments, these water-methanol mixtures are overlaid with defined amounts of particles and shaken under defined conditions (e.g., shaking gently by hand or in a tumble mixer for about 1 minute). Measurements are made of water-alcohol mixtures where the particles still do not settle, and of water-alcohol mixtures with a higher alcohol content where the particles do settle. The surface tension of the latter alcohol-water mixtures is calculated using the critical surface energy γ as a measure of the surface energy γ of the particles. crit The methanol value is calculated from the methanol content in the water.

[0074] The reinforcing filler F is preferably more hydrophobic than the silica S.

[0075] The particles P preferably have a size x 50 of 1 to 100 μm, preferably 2 to 50 μm, more preferably in particular 3 to 20 μm, and more preferably 3 to 8 μm.

[0076] The particles P are amphiphilic, which means that they are both hydrophilic (i.e. water-loving) and lipophilic (i.e. fat-loving). This means that the particles P are easily dispersible not only in polar solvents, such as, for example, water or alcohol, but also in non-polar solvents, such as, for example, aliphatic hydrocarbons, or polydimethylsiloxane oils, without the addition of further dispersing aids or additives, such as, for example, organic emulsifiers or other surface-active substances. This is a major advantage of the particles P compared to uncoated silicone elastomer particles, which are very hydrophobic and are not dispersible in polar solvents, such as, for example, water or alcohol, without the use of undesired auxiliaries, such as, for example, organic emulsifiers. In the case of the particles P, the silica S is strongly bound at the surface, so that the amphiphilicity is preserved during dispersion in the solvent. This is a major advantage compared to silicone elastomer particles according to the prior art, which are post-treated with silica after curing, because in the case of such particles not according to the invention, the absorbed silica is not permanently bound. A drawback of these particles according to the prior art is that the non-permanently bonded silica is completely or partially detached upon dispersion of the particles in a solvent, which makes the particles highly hydrophobic and no longer dispersible in polar solvents such as, for example, water.

[0077] Further provided by the present invention is a method for producing particles P consisting of a core K comprising a crosslinked silicone elastomer composition X and a reinforcing filler F and a shell H of silica S, comprising in a first step mixing a dispersion A comprising silica S and water with a mixture B comprising a crosslinkable silicone elastomer composition X and a reinforcing filler F to give a continuous phase comprising water and a discontinuous phase comprising the crosslinkable silicone elastomer composition X and the reinforcing filler F, and in a second step crosslinking the discontinuous phase to give particles P.

[0078] There is no change in the continuous phase during the crosslinking step of the second step.

[0079] The continuous phase preferably comprises at least 80 wt%, more particularly at least 90 wt% water.

[0080] A three-phase mixture (Pickering emulsion) is preferably formed, comprising an emulsion of the sparingly water-soluble and water-immiscible silicone elastomer composition X, stabilized in the aqueous phase with partially hydrophobized silica. The silicone elastomer composition X is crosslinked after emulsification in a manner suitable for the preparation of the particles P. The condensable silicone elastomer composition X may need to be hydrolyzed, for example if it comprises an alkoxy- or acetoxy-substituted silane or siloxane. If the silicone composition X is sufficiently reactive, the water present is sufficient to cause the optional hydrolysis and subsequent condensation. In the case of less reactive silicone elastomer compositions X, catalysts are required, which optionally cause the hydrolysis and condensation of the siloxanes and silanes. These catalysts may be acids, bases or metal catalysts, such as Group IV transition metal catalysts, tin catalysts, of the kind typically used to promote hydrolysis, condensation reactions or transesterification reactions. Suitable acids or bases include known mineral acids and metal salts as well as acidic or basic silanes or siloxanes.

[0081] Preferred basic catalysts are NaOH, KOH, ammonia and NEt3.

[0082] Preferred acid catalysts are p-toluenesulfonic acid, aqueous or gaseous HCl, sulfuric acid.

[0083] When the method involves a polymerization reaction, the reaction can be, for example, a radical polymerization reaction of an olefinically unsaturated siloxane or silane.

[0084] In one particular embodiment, a transition metal catalyst, such as a platinum catalyst, is added to Mixture B, for example, especially when it contains siloxanes that can react with each other in a hydrosilylation reaction.

[0085] This method should be carried out in a second step so that the silica S stabilizing the discontinuous phase reacts with the surface of mixture B forming the core during crosslinking or at least enters into stable interactions with said surface, such as hydrogen bonds, van der Waals interactions or other direct interactions, or a combination of other such direct interactions, and becomes permanently fixed on the core formed from mixture B.

[0086] The size of the particles P can be controlled, for example, through the emulsification technique, i.e., through variables such as, for example, the shear energy introduced, the volume fraction of the mixture B, the amount of silica S, the pH of the continuous aqueous phase and its ionic strength, the viscosity, the metering sequence, the metering rate, or through the reaction regime, i.e., for example, the reaction temperature, the reaction time, the concentrations of the raw materials used. The choice and amount of any hydrolysis and condensation catalysts used will also affect the particle size.

[0087] When using emulsification techniques that allow the production of relatively small droplets, the method results in small, surface-structured particles P. To this end, it is possible to use, for example, different shear energies or the selection of different silicas S to stabilize the mixture B in water.

[0088] The reinforcing filler F and any non-reinforcing fillers or any further components are mixed homogeneously with the silicone elastomer composition X in a first step, and then in a further step the mixture B is emulsified with the dispersion A and subsequently crosslinked to form the particles P. This ensures that all of the fillers and any further components are present as part of the mixture B inside the droplets after emulsification and inside the core K of the particles P after crosslinking.

[0089] Pickering emulsion E of mixture B is preferably substantially free of conventional liquid and solid organic surface-active substances that are non-particulate at room temperature and under ambient atmospheric pressure, such as nonionic, cationic and anionic emulsifiers ("organic emulsifiers").

[0090] In this specification, the organic emulsifier refers to molecules and polymers, rather than particles and colloids, in accordance with the definitions of molecules, polymers, colloids and particles described in Dispersionen und Emulsionen [Dispersions and Emulsions], G. Lagaly, O. Schulz, R. Zindel, Steinkopff, Darmstadt 1997, ISBN3-7985-1087-3, pp. 1 to 4.

[0091] Generally, these organic emulsifiers have a size less than 1 nm, a molar mass less than 10000 g / mol, a carbon content greater than 50 wt. % as determinable by elemental analysis, and a Mohs hardness less than 1.

[0092] At the same time, the organic emulsifiers which the emulsions of the invention are substantially free of usually have a solubility of more than 1 wt % in water in homogeneous or micellar form at 20° C. and the pressure of the surrounding atmosphere, i.e., 900-1100 hPa.

[0093] Pickering emulsion E of mixture B may contain such organic emulsifiers up to a maximum concentration of less than 0.1 times, preferably less than 0.01 times, more preferably less than 0.001 times, more particularly less than 0.0001 times the critical micelle concentration of these organic emulsifiers in the aqueous phase, which corresponds to a concentration of these organic emulsifiers of less than 10 wt%, preferably less than 2 wt%, more preferably less than 1 wt%, more particularly 0 wt%, based on the total weight of the dispersion of the invention.

[0094] To prepare the particle-stabilized Pickering emulsion E in a first step, all techniques known to the skilled artisan can be used for the preparation of the emulsion. However, it has been found that an emulsion that is particularly suitable for producing particles P can be obtained according to the following method.

[0095] Method 1: - initial introduction of concentrated dispersion A, the volume initially introduced is such that it contains the entire amount of silica S required, and only a partial amount of water. - Slowly meter in the entire volume of Mixture B while continuously homogenizing using, for example, a high speed stirrer, a high speed dissolver, a rotor-stator system. - Then, optionally with continuous homogenization using, for example, a high-speed stirrer, a high-speed dissolver, a rotor-stator system, slowly metered in the desired remaining volume of water.

[0096] Method 2: - initial introduction of dispersion A, the volume initially introduced is such that it contains the total amount of silica S and water required; - Slowly metered in the entire volume of mixture B while continuously homogenizing, for example with a high speed stirrer, a high speed dissolver, a rotor-stator system or with a capillary emulsifier.

[0097] Method 3: - first introduction of the entire volume of mixture B; - With continuous homogenization, for example using a high speed stirrer, high speed dissolver, rotor-stator system, the concentrated dispersion A is added slowly and quantitatively, the metered volume being such that it contains the entire amount of silica S required and only a partial amount of water. - Then, optionally with continuous homogenization using, for example, a high-speed stirrer, a high-speed dissolver, a rotor-stator system, slowly metered in the desired remaining volume of water.

[0098] Method 4: - first introduction of the entire volume of mixture B; - While continuously homogenizing, for example using a high speed stirrer, high speed dissolver, rotor-stator system, etc., Dispersion A is added slowly and quantitatively, the metered volume being such that it contains the total amount of Silica S and water required.

[0099] Method 5: - initial introduction of the total volume of mixture B and dispersion A, the volume initially introduced being such that it contains the total amount of silica S and water required; - For example, joint homogenization using high speed stirrers, high speed dissolvers, rotor-stator systems.

[0100] Method 6: - initial introduction of the total volume of mixture B and of concentrated dispersion A, the volume initially introduced being such that it contains the total amount of silica S required and a portion of the amount of water; - For example, joint homogenization using high speed stirrers, high speed dissolvers, rotor-stator systems. - Then, optionally with continuous homogenization using, for example, a high-speed stirrer, a high-speed dissolver, a rotor-stator system, slowly meter in the desired remaining volume of water.

[0101] Methods 1, 2, 5 and 6 are preferred, methods 2 and 5 are particularly preferred, and method 5 is especially preferred.

[0102] Homogenization is preferably carried out for at least 30 seconds, preferably at least 1 minute, in at least one process step.

[0103] The preparation of the dispersion A of silica S in water which forms a homogeneous phase in the emulsion of the invention can in principle be carried out according to known methods for producing particle dispersions, such as incorporation with stirring elements having a high shear action, such as high-speed stirrers, high-speed dissolvers, rotor-stator systems, ultrasonic dispersers or ball mills or bead mills.

[0104] The concentration of silica S in dispersion A here is between 1 and 80 wt%, preferably between 10 and 60 wt%, more preferably between 10 and 40 wt%, very preferably between 12 and 30 wt%.

[0105] In any process step, Pickering emulsion E is diluted with water and optionally subjected to continuous homogenization using a high speed stirrer, high speed dissolver or rotor-stator system.

[0106] The described processes may be carried out in a continuous or discontinuous manner, with the continuous mode being preferred.

[0107] The temperature in the first step is between 0°C and 80°C, preferably between 10°C and 50°C, and more preferably between 20°C and 40°C.

[0108] The emulsification operation can be carried out at atmospheric pressure, in other words, at 900 to 1100 hPa, under elevated or reduced pressure. Operation at atmospheric pressure is preferred.

[0109] The concentration of silica S in the three-phase mixture comprising dispersion A from the first step and mixture B here is between 1 and 80 wt%, preferably between 2 and 50 wt%, more preferably between 3 and 30 wt%, particularly preferably between 4 and 20 wt%.

[0110] The concentration of silicone elastomer composition X in the three-phase mixture comprising dispersion A from the first step and mixture B is between 1 and 80 wt%, preferably between 20 and 76 wt%, more preferably between 40 and 72 wt%, and particularly preferably between 50 and 70 wt%.

[0111] The concentration of water in the three-phase mixture comprising dispersion A from the first step and mixture B here is between 5 and 8 wt%, preferably between 10 and 70 wt%, more preferably between 15 and 60 wt%, particularly preferably between 20 and 40 wt%.

[0112] Starting from the above three-phase mixture, particles P can be obtained in a second step by the following method.

[0113] The three-phase mixture is preferably diluted by adding water to a mass fraction of water between 50 wt% and 90 wt%, more preferably between 40 wt% and 80 wt%.

[0114] In the second step, the particles P are preferably stirred with low shear using, for example, a low speed dissolver, rotor-stator or beam agitator in a three-phase mixer or shaken using a suitable assembly until the internal crosslinking of the particles P is complete.

[0115] The duration of the second step of the method is preferably less than 120 hours, more preferably between 0 and 48 hours, very preferably between 0.1 and 24 hours, and in one particular embodiment between 0.25 and 12 hours.

[0116] The three-phase mixture of Dispersion A and Mixture B from the first step can optionally be mixed with a catalyst as described above that accelerates and completes the crosslinking. This addition can be made directly to the discontinuous or continuous phase before the preparation of the three-phase mixture, or to the completed three-phase mixture during or after emulsification.

[0117] The amount of any catalyst added is within the typical dosage range for the catalyst.

[0118] The reaction temperature during the crosslinking phase is between 0 and 100°C, preferably between 10 and 80°C, more preferably between 15 and 60°C.

[0119] The reaction can optionally be carried out under an inert gas atmosphere, such as nitrogen, argon or carbon dioxide, in which case the oxygen fraction is less than 15 vol.%, preferably less than 10 vol.%, more preferably less than 5 vol.%.

[0120] The pH of the reaction mixture is between pH 10 and 1, preferably between pH 9 and 3, more preferably between pH 8 and 4, and in one particular embodiment between pH 7 and 5.

[0121] The three-phase mixture can optionally be mixed with a water-soluble organic solvent such as an alcohol, such as methanol, ethanol or isopropanol, or a ketone, such as acetone or MEK, or an ether, such as THF, which can be added in the first step or before or during the second step.

[0122] The three-phase mixture can optionally be mixed with dispersing aids, protective colloids and / or surfactants, which can be added in the first step or before or during the second step.

[0123] The three-phase mixture preferably contains less than 5 wt%, more preferably less than 1 wt%, and more particularly less than 0.1 wt% of dispersing aids, protective colloids, and surfactants. In one particular embodiment, the three-phase mixture is free of dispersing aids, protective colloids, and surfactants.

[0124] The three-phase mixture optionally includes an inorganic or organic electrolyte, which can be added either after the first step, during the second step, or after completion of the second step.

[0125] In this case, the ionic strength of the three-phase mixture is between 0.01 mmol / l and 1 mol / l, preferably between 0.1 mmol / l and 500 mmol / l, and more preferably between 0.5 mmol / l and 100 mmol / l.

[0126] The surface of the particles P can optionally be modified by treatment with reactive silanes or siloxanes. These can be added either in liquid or solid phase, either immediately after the preparation of the Pickering emulsion in the first step, during the reaction stage, or after the reaction stage in the second step, before the isolation of the particles P, or after the isolation of the particles. This treatment should be carried out so that the silanes or siloxanes are covalently chemically bonded to the particles. Corresponding techniques and methods are known to the skilled person.

[0127] The solids fraction of the particles P in the three-phase mixture consisting of all the solids used and of the polymerization products of materials capable of polyaddition, polycondensation or chain polymerization is between 5 wt.% and 70 wt.%, preferably between 10 wt.% and 50 wt.%, more preferably between 20 wt.% and 40 wt.%.

[0128] After the second step, the three-phase mixture can be optionally stored while still being stirred, which can be accomplished, for example, by a beam or anchor stirrer.

[0129] In one preferred embodiment the particles P are isolated, preferably by sedimentation, filtration or centrifugation, more preferably by filtration or centrifugation, very preferably by centrifugation.

[0130] After they have been isolated, the particles P are preferably washed with a washing liquid preferably chosen from fully demineralized water, methanol, ethanol and mixtures thereof.

[0131] In one preferred embodiment, the particles P are isolated in powder form from the aqueous phase, which can be achieved, for example, by filtration, sedimentation, centrifugation, or by removing volatile components by drying in an oven or dryer, or by spray drying, or by applying an appropriate reduced pressure.

[0132] Through spray drying it is possible to obtain very fine particles without further after-treatment. Particles P dried by static drying tend to form loose agglomerates which can be deagglomerated by suitable milling methods, for example by ball milling or air jet milling.

[0133] <Measurement method> - Solid content: 10 g of the aqueous dispersion is mixed with the same amount of ethanol in a porcelain dish and evaporated to constant weight in a drying cabinet purged with N2 at 150 ° C. The mass of the dry residue m S is solids / %=m s Give the solid content according to x 100 / 10g.

[0134] - Average particle size (x50): d 50was measured using a Camsizer X2 manufactured by Retsch Technology (measurement principle: dynamic image analysis according to ISO13322-2, measurement range: 0.8 μm to 30 mm, type of analysis: dry measurement of powders and granules, dispersion pressure = 2 bar).

[0135] - Carbon content %C determined by elemental analysis of carbon; combustion of the sample at over 1000°C in O2 flow, detection and quantification of the resulting CO2 by IR, instrument: LECO 244

[0136] - Methanol number: For the measurement of the methanol number, defined mixtures of water and methanol are prepared. In separate experiments, these water-methanol mixtures are layered with an equal amount of dry particles and shaken under defined conditions (e.g., shaking gently by hand or in a tumble mixer for about 1 minute).

[0137] It is determined from a water-alcohol mixture in which the particles have not yet settled and from a water-alcohol mixture with a higher alcohol content in which the particles have just settled. The methanol number is calculated from the methanol content in the water of the latter.

[0138] - Kinematic viscosity is determined according to DIN 53019 at 25°C.

[0139] In the following examples, all amounts and percentages are by weight, all pressures are 0.10 MPa (abs), and all temperatures are 20° C., unless otherwise specified in each case. EXAMPLES

[0140] [Example 1: Preparation of aqueous silica dispersion A] 200m 21300 g of partially hydrophobic pyrogenic silica with a residual silanol content of 71% and a carbon content of 0.95%, obtained by reacting a hydrophilic starting silica with a BET specific surface area of ​​1000 g / g (available from Wacker-Chemie GmbH, Munich) with dimethyldichlorosilane according to EP 1433749 A1, are incorporated in portions at 650 rpm with stirring into 5200 g of fully demineralized (FD) water in a Labo-Top planetary dissolver from PC Laborsystem, CH. After complete addition of the silica, dispersion is continued for a further 60 minutes at 650 rpm. This results in a highly viscous dispersion with a solids content of 20% and a pH of 4.2.

[0141] [Example 2: General procedure for mixing dispersion A containing silica S and water with mixture B using a dissolver] Step 1: Weigh the silica dispersion described in Example 1 into a suitable stirring vessel and stir with a Labo-Top planetary dissolver from PC Laborsystem, CH at 6000 rpm for 10 minutes. The viscosity of the dispersion is reduced. Optionally add FD water and mix homogeneously. Add the mixed silicone oil components prepared according to one of Examples 5, 6 or 7 to the stirred silica dispersion and homogenize in the dissolver at 6000 rpm with water coolant for 10 minutes. During this time, the temperature of the mixture should not exceed 35°C. The result is a viscous white mass.

[0142] Step 2: The thick mass from step 1 of the method is diluted with three portions of the same amount of FD water to a silicone oil content of 30% at 1000 rpm. After each portion of FD water, stir for 3 minutes at 1000 rpm. This results in a highly fluid, white O / W emulsion.

[0143] [Example 3: General procedure for mixing dispersion A containing silica S and water with mixture B using an Ultra-Turrax] Step 1: Weigh the silica dispersion described in Example 1 into a suitable 1000ml / l stainless steel container and use Ultra-Turrax T50 to stir at 10000rpm for 10 minutes. The viscosity of the dispersion is reduced. Optionally add FD water and mix homogeneously. Add the mixed silicone oil components prepared according to one of Examples 5, 6 or 7 to the stirred silica dispersion and homogenize with Ultra Turrax at 10000rpm for 10 minutes while cooling with ice. During this time, the temperature of the mixture should not exceed 35°C. The result is a viscous white mass.

[0144] Step 2: Dilute the thick mass from step 1 to 30% silicone oil content by adding 3 portions of the same amount of FD water. After each portion of FD water, mix at 6000 rpm for 3 minutes. This results in a highly fluid, white O / W emulsion.

[0145] Example 4: General procedure for producing the inventive silica-coated silicone elastomer microparticles P from a Pickering emulsion of mixture B. 250 g of the Pickering emulsion susceptible to polyaddition prepared according to Example 2 or Example 3 was mixed with 1000 mm 2 The resulting mixture, in the form of a 1 wt. % solution in polydimethylsiloxane containing vinyl groups at 1000 rpm (25° C.), is mixed with 20 ppm (based on the amount of platinum) of Karstedt catalyst using a paddle stirrer at 200 rpm and the mixture is stirred at 80° C. for 24 hours. The result is a white, highly fluid dispersion. For isolation, the particles P are removed by filtration and dried in a drying cabinet at 80° C. for 24 hours. This gives a fine, white powder.

[0146] [Example 5: Silicone resin reinforced mixture B susceptible to polyaddition] Viscosity 1000mm 2 / sec (25°C) and 375 g of vinyldimethylsiloxy-terminated polydimethylsiloxane with a viscosity of 20,000 mm 2264 g of a vinyldimethylsiloxy-terminated polydimethylsiloxane having a viscosity of 100 MPa (25° C.) was mixed homogeneously using a paddle stirrer. 1 / 2 ] 26.65 [ViMe2SiO 1 / 2 ] 3.72 [SiO 4 / 2 ] 42.78 [HO 1 / 2 ] 1.02 [EtO 1 / 2 ] 5.93 274 g of a silicone resin containing vinyl groups (molecular weight by SEC (eluent, toluene): Mw = 5300 g / mol, Mn = 2560 g / mol) was added and the mixture was stirred until dissolution was complete. The base mass thus obtained was mixed with a 40 mm viscosity at 25°C. 2 / sec., and intimately mixed with 114 g of a copolymer composed of dimethylsiloxy units, methylhydrogensiloxy units and trimethylsiloxy units and having a SiH content of 0.40%.

[0147] [Example 6: Production of silicone elastomer particles P coated with silica and reinforced with silicone resin] 320 g of the inventive mixture B from Example 5 and 240 g of the aqueous silica dispersion A from Example 1 were emulsified as in Example 2. Subsequently, pulverized silicone elastomer particles P were produced as in Example 4, with an average particle size of d 50 =3.4 μm.

[0148] Example 7: Silica-reinforced Mixture B susceptible to polyaddition The first commercially available experimental mixer was a 1000mm viscosity mixer. 2 917 g of vinyldimethylsiloxy-terminated polydimethylsiloxane with a specific surface area of ​​125 m was heated to 150°C. 2 / g (measured by the BET method) and mixed with 621 g of hydrophobic pyrogenic silica with a carbon content of 1.6-2.0 wt%. This gave a highly viscous mass which was subsequently diluted with 618 g of the aforementioned polydimethylsiloxane. Kneading at 150°C under reduced pressure (10 mbar) allowed the mass obtained to be freed from moisture and excess residues of the loading agent, especially volatile components, within 1 hour. It was then cooled to a viscosity of 100 mm at 25°C. 2 123 g of a copolymer composed of dimethylsiloxy units, methylhydrogensiloxy units and trimethylsiloxy units with a SiH content of 0.47% is added at 1000 g / sec and mixed homogeneously.

[0149] [Example 8: Production of silica-coated and silica-reinforced silicone elastomer particles P] 156 g of the inventive mixture B from Example 7 and 149 g of the aqueous silica dispersion A from Example 1 were emulsified as in Example 3. Subsequently, ground silicone elastomer particles P were produced as in Example 4, with an average particle size of d 50 =12 μm.

[0150] Comparative Example C1: Silicone elastomer composition that does not contain a reinforcing filler and is susceptible to polyaddition Both chain ends are blocked with dimethylvinylsilyl groups. Viscosity 1000mm 2 1535 g of polydimethylsiloxane containing vinyl groups with a viscosity of 100 mm / sec (25°C) was used without adding any reinforcing additives. 2 The mixture was homogeneously mixed with 123 g of a copolymer composed of dimethylsiloxy units, methylhydrogensiloxy units and trimethylsiloxy units having a viscosity of 1000 g / sec and a SiH content of 0.47% using a paddle stirrer.

[0151] Comparative Example C2: Preparation of Silica-Coated Silicone Elastomer Particles Containing No Reinforcing Filler 320 g of the silicone elastomer composition not according to the invention from Comparative Example C1 and 240 g of the aqueous silica dispersion from Example 1 were emulsified according to Example 2. Then, according to Example 4, ground silicone elastomer particles were produced, the average particle size of which was d50 =18 μm.

[0152] Comparative Example C3: Silicone elastomer composition that does not contain a reinforcing filler and is susceptible to polyaddition. Both chain ends are blocked with dimethylvinylsilyl groups. Viscosity 200mm 2 / sec (25 °C), and 479 g of polydimethylsiloxane containing vinyl groups, with a viscosity of 65 mm 2 % of a trimethylsilyl-terminated methylhydrosiloxane-dimethylsiloxane copolymer containing 0.73 wt % Si-bonded hydrogen at 25° C. / s was mixed to homogeneity using a paddle stirrer.

[0153] Comparative Example C4: Preparation of Silicone Elastomer Particles Coated with Silica Containing No Reinforcing Filler 320 g of the silicone elastomer composition not according to the invention of Comparative Example C3 and 240 g of the aqueous silica dispersion of Example 1 were emulsified according to Example 2. Then, according to Example 4, ground silicone elastomer particles were produced, the average particle size of which was d 50 =9 μm.

[0154] [Example 9: Sensory evaluation of particles P] The sensory evaluation of the inventive silica-coated silicone elastomer particles P from Examples 6 and 8, and of the particles from Comparative Examples C2 and C4 not according to the invention, was carried out by a trained team of five testers.

[0155] For the evaluation, subjects washed their hands and lower arms with soap and water. A circular test area 4 cm in diameter for each sample was drawn on the lower arm and 0.04 g of each particle was applied and sprayed each time.

[0156] The parameters evaluated by the testers were silkiness during application and skin feel after application of the powder was complete, based on a scale of 0 (poor) to 4 (very good). The results are shown in Table 1.

[0157] [Table 1]

[0158] Example 10: Mechanical integrity of particles P In contrast to Example 9, the tester applied the particles to the skin under strong pressure. The results for the inventive silica-coated silicone elastomer particles P from Examples 6 and 8 were unchanged, whereas the particles from Comparative Examples C2 and C4, which are not according to the invention, formed lumps during application, which is undesirable in cosmetic applications.

[0159] [Table 2]

[0160] [Example 11: Evaluation of mechanical strength] The inventive silica-coated silicone elastomer particles P from Examples 6 and 8, and the particles from Comparative Examples C2 and C4, which are not according to the invention, were mixed with 100% by weight of 2 mm viscous silica. 2 1000g / s (25°C). The particles swell and completely absorb the silicone oil.

[0161] The swollen particles were then tested on the skin in a similar manner to Example 9. Surprisingly, it was found that the inventive silica-coated silicone elastomer particles from Examples 6 and 8 exhibit a very good velvety to silky smooth skin feel after application, whereas the particles from Comparative Examples C2 and C4, which are not according to the invention, have a much waxier skin feel after application and spread more slowly.

[0162] [Table 3]

Claims

1. Particle P is composed of a core K containing a crosslinked silicone elastomer composition X and a reinforcing filler F and a shell H of silica S.

2. The silicone elastomer composition X is addition crosslinked, (A) at least one linear compound containing a group having an aliphatic carbon-carbon multiple bond; (B) at least one linear organopolysiloxane compound having Si-bonded hydrogen atoms; or instead of (A) and (B): (C) at least one linear organopolysiloxane compound containing an aliphatic carbon-carbon multiple bond and a SiC-bonded group having a Si-bonded hydrogen atom; and (D) at least one hydrosilylation catalyst; The particle P according to claim 1 , comprising:

3. The reinforcing filler F has a BET specific surface area according to DIN 66131 of at least 50 m 2 / g of pyrogenic or precipitated hydrophobic silica, and from carbon black and activated carbon and silicone resins.

4. Particles P according to any one of claims 1 to 3, wherein said reinforcing filler F has a methanol number of more than 40 due to the surface treatment.

5. 5. P particles according to claim 1, wherein the core K comprises 5 to 200 parts by weight of a reinforcing filler F per 100 parts by weight of the crosslinkable silicone elastomer composition X.

6. The silica S is at least 50 m 2 Particles P according to any one of claims 1 to 5, which are chosen from pyrogenic or precipitated hydrophobic silicas having a BET specific surface area of ​​100 / g.

7. Particles P according to any one of claims 1 to 6, wherein said reinforcing filler F is more hydrophobic than silica S.

8. A method for producing particles P according to any one of claims 1 to 7, comprising the steps of: In a first step, a dispersion A containing silica S and water is mixed with a mixture B containing a crosslinkable silicone elastomer composition X and a reinforcing filler F to obtain a continuous phase containing water and a discontinuous phase containing the crosslinkable silicone elastomer composition X and the reinforcing filler F, In a second step, the discontinuous phase is crosslinked to obtain particles P.

9. The method of claim 8 , wherein the continuous phase comprises at least 80 wt % water.

10. 10. The method according to claim 8 or 9, in which in the first step, the entire volume of mixture B and dispersion A is initially introduced, such that the initially introduced volume contains the entire amount of silica S and water required.

11. The method according to any one of claims 8 to 10, wherein in the first step a catalyst is added to crosslink the crosslinkable silicone elastomer composition X.

Citation Information

Patent Citations

  • Particles with structured surface

    WO2007113095A1

  • Silica-coated silicone rubber particles and cosmetic

    WO2017142068A1